127 Relationship between plasma concentrations of b-type natriuretic peptide and exercise capacity in hypertrophic cardiomyopathy. (5th June 2017) - Lota, Amrit; Mouy, Florence; Wassall, Rebecca; Newsome, Simon; Halliday, Brian; Baksi, John; Pantazis, Antonis; Ware, James; Cook, Stuart; Pennell, Dudley; Cleland, John; Prasad, Sanjay
Abstract : Background: Hypertrophic cardiomyopathy (HCM) is characterised by increased left ventricular wall thickness leading to exercise intolerance and heart failure. Peak oxygen consumption (peak VO2) on cardiopulmonary exercise testing (CPET) is often used as a functional marker alongside B-type natriuretic peptide (BNP). However, CPET is complex and time-consuming, access may be limited, and peak VO2 can be influenced by physical deconditioning and motivation. Our aims were to determine the association between BNP and submaximal exercise parameters, ventilatory efficiency (VE/VCO2) and anaerobic threshold; and to determine whether f these were effective surrogate markers of functional status in patients with HCM. Methods: We retrospectively reviewed data for all patients with HCM in our local cardiomyopathy service. A diagnosis of HCM was based on LV hypertrophy >15 mm as per current ESC guidelines. Patients underwent contemporaneous echocardiography, CPET using maximal treadmill ergometry and BNP measurement at sequential annual clinic visits [1 (18%), 2 (52%), 3 (20%) or ≥4 visits (10%)] yielding data from 252 observations over 8 years for 119 individual patients. Univariable and multivariable linear regression was used to investigate variables associated with the results of CPET. Robust standard errors were used to correct for multiple observations from the same patients. Results: In our cohort of 119 patients (mean age 49±17 years, 66% men), mean LVEF was 75±7%, maximal wall thickness was 19±5 mm, and left ventricular outflow tract obstruction was present in 15%. The mean peak V02 was 26±8 L/min, mean VE/VCO2 slope was 30±6 and median BNP was 93.5 ng/L (IQR 43.5–232.5). On univariable analysis, several markers were found to predict peak VO2; age (β²=−4.5; 95% CI −6.1 – −3.0; p<0.00001), male sex (β²=5.2; 95% CI 2.3 – 8.1; p<0.001), LV ejection fraction (β²=−2.1; 95% CI −3.6 – −0.6; p<0.01), BNP (β²=−4.0; 95% CI −5.8 – −2.2; p<0.0001) and echocardiographic markers of diastolic dysfunction, for example, E/E lateral ratio (β²=−3.4; 95% CI −4.8 – −2.0; p<0.00001). Predictors of VE/VCO2 were age (β²=1.5; 95% CI 0.6 – 2.3; p<0.01), BNP (β²=2.4; 95% CI 1.5 – 3.4; p<0.00001) and similar echocardiographic markers of diastolic dysfunction. Multivariable analysis revealed that BNP was associated with peak VO2 (β²=−2.0; 95% CI −3.0 – −1.1; p<0.0001) but also age, male sex, indexed RV end-?diastolic volume and body weight, whilst BNP was independently associated with VE/VCO2 (β²=0.8; 95% CI 0.1 – 1.6; p<0.001), and to a lesser extent, anaerobic threshold (β²=−1.4; 95% CI −2.2 − −0.6; p=0.001). Conclusion: In this cohort, BNP is independently associated with VE/VCO2, a marker of ventilation-perfusion mismatch, which is known to provide a more reliable assessment of exercise intolerance irrespective of effort level. These results therefore support a role for BNP as an useful marker of submaximal exercise capacity and for consideration in guiding prognosis.